"I Am Malcolm X" – Islamic Themes in Hip‐hop Video Clips Online. Issue 2 (1st September 2014) - Ackfeldt, Anders
Abstract: The Internet provides a space for new interpretations and conversations concerning religious practices to take place without the direct interference of religious authorities. The intention of this article is to highlight one vivid aspect of this development, Islamic themed hip-hop video clips distributed online. The visual aesthetics, the selection of pictures (or no pictures), themes and storylines supplementing the musical message can be used to mobilize and promote different traditions of interpretation of Islam. They can also convey interesting insights in the negotiations and compromises of Muslim identities in the consumer culture logic of the modern society. Lastly, they can provide a route to analyze the articulations of alternative interpretations of Islam often, but not always, rooted in a deep social-justice activism that connects marginalized communities within and beyond the Middle East